السرية النبوية من خالل خمطوطات احلكاايت والقصص أبرخبيل املاليو: دراسة حتليلية - Adel M. AbdulAziz Al Geriani; Nidzamuddin Zakaria (UNISZA, 2024)
It was known about Malay literature before the dawn of Islam on these lands that it was an oral literature of a mythical character, full of doctrines and fictional stories most of them translated from Indian literature, and after the advent of Islam, the Malay community got acquainted with the literature of written stories through the Middle East, so they distinguished and excelled in it, especially those stories and the stories related to the prophetic literature, which are stories that tell the life of the Prophet Muhammad and other prophets, messengers and companions, and a number of tales and stories about the Prophet Muhammad were found in ancient Malay literature, including tales about his birth, stories about his miracles, his conquests, some of his wives, his miracles, etc. Through this study and following the descriptive and analytical approaches, we seek to uncover other unknown pages of the contributions of scholars of the Malay Archipelago in the field of prophetic biography, and to explain their methodology, style and sources in it.